DRAM for distilling microbial metabolism to automate the curation of microbiome function. Issue 16 (7th August 2020) - Shaffer, Michael; Borton, Mikayla A; McGivern, Bridget B; Zayed, Ahmed A; La Rosa, Sabina Leanti; Solden, Lindsey M; Liu, Pengfei; Narrowe, Adrienne B; Rodríguez-Ramos, Josué; Bolduc, Benjamin; Gazitúa, M Consuelo; Daly, Rebecca A; et al.
Abstract: Microbial and viral communities transform the chemistry of Earth's ecosystems, yet the specific reactions catalyzed by these biological engines are hard to decode due to the absence of a scalable, metabolically resolved, annotation software. Here, we present DRAM (D istilled and R efined A nnotation of M etabolism), a framework to translate the deluge of microbiome-based genomic information into a catalog of microbial traits. To demonstrate the applicability of DRAM across metabolically diverse genomes, we evaluated DRAM performance on a defined, in silico soil community and previously published human gut metagenomes. We show that DRAM accurately assigned microbial contributions to geochemical cycles and automated the partitioning of gut microbial carbohydrate metabolism at substrate levels. DRAM-v, the viral mode of DRAM, established rules to identify virally-encoded auxiliary metabolic genes (AMGs), resulting in the metabolic categorization of thousands of putative AMGs from soils and guts. Together DRAM and DRAM-v provide critical metabolic profiling capabilities that decipher mechanisms underpinning microbiome function.